Shear capacity of composite slab reinforced with steel fibre to that of fabric reinforcement in concrete topping - Ibrahim, Izni Syahrizal (Maney Publishing, 2014)
This paper presents the experimental result on the shear capacity of composite slab reinforced with steel fibre concrete topping. Experimental test is carried out on 75 composite slab specimens reinforced with various steel fibres volume fractions in the concrete topping. The type of steel fibres is varied to determine the suitable type to be applied in the concrete topping. This includes HE075/60, HE075/50 and HE055/33 referred to as SF60, SF50 and SF33, respectively, in this paper. The test parameters are fibre aspect ratio, volume fraction and fibre reinforcing index. Control specimen using prefabricated welded steel mesh in the concrete topping is also tested for comparison. The test results show that by replacing prefabricated welded steel mesh with steel fibre in the concrete topping increased the shear capacity of the composite slab. However, the increment depends on the type of steel fibre, where the optimum increment for SF60 and SF50 started at Vf = 075% whereas for SF33 at Vf = 025%. Even though the percentage increment is small from the whole capacity of the composite slab, but the steel fibre is able to arrest cracks once the propagation started to reach the concrete topping zone during the post-cracking development. This is important especially to members subjected to high shear load, where steel fibres can create an additional shear carriage capacity by preventing them from sudden failure.